2019
DOI: 10.1371/journal.pone.0223623
|View full text |Cite
|
Sign up to set email alerts
|

Robust automated reading of the skin prick test via 3D imaging and parametric surface fitting

Abstract: The conventional reading of the skin prick test (SPT) for diagnosing allergies is prone to inter- and intra-observer variations. Drawing the contours of the skin wheals from the SPT and scanning them for computer processing is cumbersome. However, 3D scanning technology promises the best results in terms of accuracy, fast acquisition, and processing. In this work, we present a wide-field 3D imaging system for the 3D reconstruction of the SPT, and we propose an automated method for the measurement of the skin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It was concluded that the agreement between the device and the manual procedure was moderate (25) . Other methods supporting the automated read out of the SPT results are based on 3D imaging (26) or are using a combination of visible-spectrum and thermal images (27) .…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the agreement between the device and the manual procedure was moderate (25) . Other methods supporting the automated read out of the SPT results are based on 3D imaging (26) or are using a combination of visible-spectrum and thermal images (27) .…”
Section: Discussionmentioning
confidence: 99%
“…The method proposed by Pineda et al [9] consisted of multiple stages. First, the wheals are detected via multi-scale filtering with Laplacian of Gaussians, second decomposing the image into patches, and third determining their centers of mass using PCA.…”
Section: Methodsmentioning
confidence: 99%
“…The images used to train and validate the neural network are the same from Pineda et al [9], in which the fringe projection system shown in Fig. 3 is used, and the 3D images of the forearm are like the one shown in Fig.…”
Section: A Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Base surface removal of each 3D image is performed using the pyramid decomposition method. 11 This approach, in Fig. 2, for the Base Surface Removal stage relies on a standard Gaussian-Laplacian pyramid 12 to obtain S′ from the 3D image, S. A Gaussian pyramid decomposes S into subsets of progressively lower resolution image versions G l , which are then down-sampled and iterated n times for each level until G n has only a few pixels.…”
Section: Base Surface Removalmentioning
confidence: 99%